Changes in functional network centrality underlie cognitive dysfunction and physical disability in multiple sclerosis. (July 2014) - Schoonheim, M M; Geurts, J J G; Wiebenga, O T; De Munck, J C; Polman, C H; Stam, C J; Barkhof, F; Wink, A M
Background: Cognitive dysfunction in multiple sclerosis (MS) has a large impact on the quality of life and is poorly understood. Objective: The aim of this study was to investigate functional network integrity in MS, and relate this to cognitive dysfunction and physical disability. Methods: Resting state fMRI scans were included of 128 MS patients and 50 controls. Eigenvector centrality mapping (ECM) was applied, a graph analysis technique that ranks the importance of brain regions based on their connectivity patterns. Significant ECM changes were related to physical disability and cognitive dysfunction. Results: In MS patients, ECM values were increased in bilateral thalamus and posterior cingulate (PCC) areas, and decreased in sensorimotor and ventral stream areas. Sensorimotor ECM decreases were related to higher EDSS (rho = −0.24, p = 0.007), while ventral stream decreases were related to poorer average cognition (rho = 0.23, p = 0.009). The thalamus displayed increased connectivity to sensorimotor and ventral stream areas. Conclusion: In MS, areas in the ventral stream and sensorimotor cortex appear to become less central in the entire functional network of the brain, which is associated with clinico-cognitive dysfunction. The thalamus, however, displays increased connectivity with these areas. These findings may aid in further elucidating the function of functional reorganization processes in MS.